(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2022)
In these pages we will reflect on the female protagonists of the traditional versions of Folk tales and their controversial role in terms of gender stereotypes. Based on the versions of some of the lesser-known stories of the Hispanic tradition (such as The girl who waters the basils), the study will lead to a reflection on equality from a gender perspective in current children’s literature. It will focus on the novel Indomia, by I.C. Viro (2019), which also has an indomitable protagonist. We believe that, in order to offer a realistic vision of the subject, it is necessary to know not only the most famous adaptations but also the popular versions of the aforementioned stories, which are a clear antecedent of the brave protagonists of contemporary children’s literature. Finally, the results of a didactic experience in the University classrooms (based on the tale) are presented.